1987
DOI: 10.1126/science.3499668
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Liver-Specific Nuclear Factor with the Fibrinogen and α 1 -Antitrypsin Promoters

Abstract: The orderly and sequential activation of genes during development is hypothesized to be related to the selective expression of groups of regulatory proteins acting primarily at the level of transcription. A nuclear protein was found in hepatocytes, but not other cell types, that binds to a sequence required for hepatocyte-specific transcription of the gene for the beta chain of fibrinogen. This protein, hepatocyte nuclear factor 1 (HNF1), also interacts with homologous sequences required for optimal promoter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
299
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(306 citation statements)
references
References 25 publications
6
299
0
1
Order By: Relevance
“…TCF1 and TCF2, respectively, encode the transcription factors hepatocyte nuclear factor 1a and b (HNF1a and HNF1b), two POU-homeodomain proteins that bind to an essential element in the proximal promoter sequences of albumin and many other tissue-specific genes and are associated with development, metabolism and cancer (Cereghini et al, 1987;Courtois et al, 1987;Frain et al, 1989;Rey-Campos et al, 1991). For instance, TCF2 defects cause developmental abnormalities in multiple tissues, including kidney and pancreas (Horikawa et al, 1997;Haumaitre et al, 2005), and Bluteau et al (2002) identified biallelic mutations of TCF1 in hepatic adenomas (Bluteau et al, 2002).…”
mentioning
confidence: 99%
“…TCF1 and TCF2, respectively, encode the transcription factors hepatocyte nuclear factor 1a and b (HNF1a and HNF1b), two POU-homeodomain proteins that bind to an essential element in the proximal promoter sequences of albumin and many other tissue-specific genes and are associated with development, metabolism and cancer (Cereghini et al, 1987;Courtois et al, 1987;Frain et al, 1989;Rey-Campos et al, 1991). For instance, TCF2 defects cause developmental abnormalities in multiple tissues, including kidney and pancreas (Horikawa et al, 1997;Haumaitre et al, 2005), and Bluteau et al (2002) identified biallelic mutations of TCF1 in hepatic adenomas (Bluteau et al, 2002).…”
mentioning
confidence: 99%
“…Nuclear extracts were prepared from mouse and rat tissues with minor modification of published methods (Courtois et al 1987). Briefly, tissues were excised immediately after the animals were sacrificed and homogenized in ice-cold buffer A [10 mM HEPES (pH 7.8 at 4°C), 15 mM KC1, 2 mM MgC12, 1 mM DTT, 0.1 mM EDTA, 1 mM PMSF, 10 lag/ml leupeptin, and 1 txg/ml antipain].…”
Section: Nuclear Extractionsmentioning
confidence: 99%
“…Furthermore, we find that heterodimerization is regulated in a tissue-specific manner, as freely exchangeable heterodimers are formed in transfected Jurkat human T cells but stable nonexchangeable homodimers are present in liver extracts. For simplicity we will use the terms HNF-I~ for the original HNF-1 protein (Courtois et al 1987) and HNF-I~ for the newly cloned vHNF-1 Cereghini et al 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Upstream of this region at position -86 and -107 the nucleotide sequence contains two half-recognition sites for the nuclear factor NFl: consensus sequence, 5'-TGG(A/C)N5G-CCAA-3' [23]. An absolute homology was found to the ATTAAC motif reported to mediate liver-specific expression by hepatocyte nuclear factor HNF1 [24] at position -171 to -176. DISCUSSION H.p.l.c.…”
Section: Pgth2mentioning
confidence: 98%